Magnetic Nanoparticle-Assisted Tunable Optical Patterns from Spherical Cholesteric Liquid Crystal Bragg Reflectors - Yali Lin; Yujie Yang; Yuwei Shan; Lingli Gong; Jingzhi Chen; Sensen Li; Lujian Chen (Nanomaterials, 2017)
Cholesteric liquid crystals (CLCs) exhibit selective Bragg reflections of circularly polarized (CP) light owing to their spontaneous self-assembly abilities into periodic helical structures. Photonic cross-communication patterns could be generated toward potential security applications by spherical cholesteric liquid crystal (CLC) structures. To endow these optical patterns with tunability, we fabricated spherical CLC Bragg reflectors in the shape of microshells by glass-capillary microfluidics. Water-soluble magnetofluid with Fe3O4 nanoparticles incorporated in the inner aqueous core of CLC shells is responsible for the non-invasive transportable capability. With the aid of an external magnetic field, the reflection interactions between neighboring microshells and microdroplets were identified by varying the mutual distance in a group of magnetically transportable and unmovable spherical CLC structures. The temperature-dependent optical reflection patterns were investigated in close-packed hexagonal arrangements of seven CLC microdroplets and microshells with inverse helicity handedness. Moreover, we demonstrated that the magnetic field-assisted assembly of microshells array into geometric figures of uppercase English letters “L” and “C” was successfully achieved. We hope that these findings can provide good application prospects for security pattern designs.